2017
DOI: 10.1111/cei.13003
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 ameliorates renal fibrosis by simultaneously affecting leucocyte recruitment and TGF-β signalling in fibroblasts

Abstract: Renal fibrosis is the common final manifestation of chronic kidney diseases and usually results in end-stage renal failure. In this study, we evaluated the effect of fingolimod (FTY720), an analogue of sphingosine 1-phosphate (S1P), as a treatment for the unilateral ureteral obstruction (UUO)-induced renal fibrosis animal model. We treated mice with FTY720 at a dosage of 1 mg/kg/day by intragastric administration from day 1 until day 7. The control group received the same amount of saline. FTY720 reduced signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…According to previous studies and our CCK-8 results, 10 ng/mL TGF-β1 was used to activate fibroblasts; 1, 2, and 4 mg/mL were selected as the low-, moderate- and high-doses of SK; and 48 h was selected as the intervention time in the present study. Upregulation of α-SMA and morphological changes accompanied by cell proliferation and activation, which manifested as increases in cell viability and ECM production, occurred in NRK-49F cells after TGF-β1 stimulation [ 26 , 27 ]. In this study, it was confirmed that TGF-β1 regulated the gene expression of α-SMA and ECM by activating the upstream JAK2/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies and our CCK-8 results, 10 ng/mL TGF-β1 was used to activate fibroblasts; 1, 2, and 4 mg/mL were selected as the low-, moderate- and high-doses of SK; and 48 h was selected as the intervention time in the present study. Upregulation of α-SMA and morphological changes accompanied by cell proliferation and activation, which manifested as increases in cell viability and ECM production, occurred in NRK-49F cells after TGF-β1 stimulation [ 26 , 27 ]. In this study, it was confirmed that TGF-β1 regulated the gene expression of α-SMA and ECM by activating the upstream JAK2/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently demonstrated that ApoM/S1P possesses protective properties against LPS‐induced renal injuries through their antiapoptotic properties (44). Regarding models of chronic kidney diseases, however, the roles of S1P have yet to be established, and the involvement of ApoM has not been studied, although S1P has been demonstrated to possess profibrotic properties (4547). Therefore, investigation of the roles of S1P in chronic kidney diseases, especially using in vivo experiments, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, by attenuating expression of intrarenal angiotensin II and AT1R, a combination of telmisartan and pitavastatin could inhibit renal fibrosis and inflammation by suppressing activations of TGF-β1-Smad and NF-κB [110]. Fingolimod (FTY720), an analogue of sphingosine 1-phosphate, has been shown to attenuate collagen deposition, inflammation and tubulo-interstitial fibrosis in UUO mice [175]. Furthermore, FTY720 mitigated TGF-βmediated α-SMA expression and collagen synthesis by inhibiting both Smad2/3 and PI3K/AKT/glycogen synthase kinase 3 beta pathways in NRK-49F cells [175].…”
Section: Selective Inhibition Of Smads Signalingmentioning
confidence: 99%
“…Fingolimod (FTY720), an analogue of sphingosine 1-phosphate, has been shown to attenuate collagen deposition, inflammation and tubulo-interstitial fibrosis in UUO mice [175]. Furthermore, FTY720 mitigated TGF-βmediated α-SMA expression and collagen synthesis by inhibiting both Smad2/3 and PI3K/AKT/glycogen synthase kinase 3 beta pathways in NRK-49F cells [175]. Ki16425, a LPA receptor 1/3 antagonist, has been shown to block upregulation of TGF-β1 expression and Smad2/3 phosphorylation in SV40 MES13 cells by lysophosphatidic acid stimulation and in db/db mice [176].…”
Section: Selective Inhibition Of Smads Signalingmentioning
confidence: 99%